Is Your Tutorial Pretty or Pretty Useless? Creating Effective Tutorials with the Principles of Multimedia Learning. Issue 1 (2nd January 2017) - Rapchak, Marcia E.
ABSTRACT: With the proliferation of free and easy-to-use tools to make online tutorials, many libraries have been creating online tutorials for their users. These cover everything from showing users how to navigate the databases to covering issues like copyright and evaluation. While the tutorials range from entertaining to rather dry, many of them, regardless of their entertainment value, do not employ the methods that can lead to deeper learning. Mayer (2014a ) has explored the concepts and research around online tutorials in The Cambridge Handbook of Multimedia Learning. The principles covered in the handbook and in the related research can be quite counterintuitive for those of us who create online tutorials. This article explores these principles as they relate to tutorials created for library instruction. Additional research to expand on and support Mayer's principles will be discussed to provide evidence-based strategies for deepening learning and reducing elements that detract from learning.